Behavioral difficulties, sleep problems, and nighttime pain in children with cerebral palsy. (December 2019) - Horwood, Linda; Li, Patricia; Mok, Elise; Oskoui, Maryam; Shevell, Michael; Constantin, Evelyn
Highlights: 25% of children with cerebral palsy (CP) have behavioral difficulties. Behavioral difficulties are 2-fold higher in school vs. preschool children with CP. Sleep problems were most strongly associated with behavioral difficulties. Nighttime pain was also strongly associated with behavioral difficulties. Abstract: Background: Children with cerebral palsy (CP) may be at risk of behavioral difficulties. Aims: 1) Determine the prevalence of behavioral difficulties in preschool- and school-aged children with CP and 2) Assess the association between behavioral difficulties and a) sleep problems, b) nighttime pain and c) child characteristics (age, CP phenotype, comorbidities). Methods and procedures: Caregivers of 113 children with CP aged 4–12 years [mean (SD) age = 7.4 (2.5) years; 61.9% male] completed the Strengths and Difficulties Questionnaire, Sleep Disturbance Scale for Children and a sleep quality questionnaire to assess child behavior, sleep and nighttime pain, respectively. Outcomes and results: 25.6% of children (17.6% preschool-aged; 29.1% school-aged) had behavioral difficulties. Sleep problems (odds ratio [OR] 9.1, 95% confidence interval [CI] 3.4–24.4) and nighttime pain (OR 4.1, 95% CI 1.5–11.5) were associated with behavioral difficulties. Sleep problems remained significantly associated with behavioral difficulties (adjusted OR 7.5, 95% CI 2.6–21.4) when adjusted for nighttime pain, age and non-ambulatory status. Conclusions and implications: Behavioral difficulties were reported in one in four children with CP and were associated with sleep problems and nighttime pain. Identifying and treating behavioral difficulties, sleep problems or nighttime pain is important in the care of children with CP.